Dasar Hukum Penuntut Umum Mengajukan Kasasi Terhadap Putusan Lepas Dari Segala Tuntutan Hukum Dalam Perkara Penggelapan Dalam Jabatan Secara Berlanjut - Alfian Nanung Pradana (Verstek, 2017)
The purpose of this research is to know the legal status of the public prosecutor in filing appeal against matters of embezzlement in Office continuously charged with Article 64 paragraph (1) Jo. Article 32 of the Criminal Code.     This study discusses the embezzlement in Office continuously conducted Sharif Muda Siregar, S.E., West. The Act of the defendant that is several times has been taking money from the Treasurer of the school which should belong to the Foundation and use it for the benefit of outside Islamic College Foundation's interests rather than "Nurul Ilmi" educational institutions BM Muda Padangsidempuan which totals Rp 33.779.500 RP (thirty-three million seven hundred seventy-nine thousand five hundred rupiah). On that basis the Sharif Muda Siregar, S.E., West., was tried in the District Court of Padangsidempuan. District Court defendant innocent Padangsidempuantermination on the basis of the consideration of the Tribunal is Judge because it found the existence of reasons of forgiving so that the Act of the defendant be delete/missing altogether.      The results showed that the legal basis for the public prosecutor in asking the StateCourt judge of Cassation is Padangsidempuan misinterpret elements against the law contained in article 372 of the Criminal Code so as to categorize the Act of the defendant as the Act by reason of forgiving (overmacht). The public prosecutor filed an appeal over the decision of a District Court and granted by Padangsidempuan Supreme Court approved the reasons of Cassation Prosecutor that State Court Padangsidempuan misinterpreted law.       Keywords: appeal, the verdict, Prosecutor General, Supreme Court